Perubahan Iklim dan Krisis Lingkungan: Tantangan Hukum dan Peran Masyarakat (International Forum of Researchers and Lecturers, 2024)
Climate change and environmental crisis are two intertwined global issues that pose major challenges to humanity in the 21st century. Their impacts are already being felt around the world, threatening the survival of humans, ecosystems, a0nd planet Earth. This article discusses the legal challenges and community roles in addressing climate change and environmental crisis. In the first section, the article explains the definition, causes, and impacts of climate change and environmental crisis globally and in Indonesia. The second section examines various legal instruments that have been formulated at international, national, and local levels to address climate change and environmental crisis. In this section, the article analyzes the effectiveness and challenges in implementing these legal instruments. The third section focuses on the role of communities in efforts to combat climate change and environmental crisis. The article highlights various actions and initiatives that can be taken by individuals, communities, and civil society organizations. In conclusion, the article emphasizes that climate change and environmental crisis require comprehensive solutions involving various parties, including governments, the private sector, and communities. Strong legal instruments and their effective implementation are crucial, but the active role of communities in real action and policy advocacy is equally important.